The role of state mindfulness during yoga in predicting self-objectification and reasons for exercise. (January 2016) - Cox, Anne E.; Ullrich-French, Sarah; Cole, Amy N.; D'Hondt-Taylor, Margo
Abstract: Objectives: Objectification theory is a useful framework for understanding how individuals internalize the sexual objectification of male and female bodies. This internalization, called self-objectification, can result in negative psychological and behavioral outcomes (e.g., body shame, disordered eating). Exercise that uses mindfulness to draw attention to the body's function and sensations rather than appearance may be one way to minimize self-objectification and improve associated outcomes. Therefore, the objective of this study was to explore how state mindfulness during exercise may associate with change in self-objectification, body image variables, and reasons for exercise. Design: This study prospectively followed participants ( N  = 148, 80% female) from six yoga classes that met 2–3 times a week across an 8-week period. Method: Repeated measures MANOVAs were used to examine change over time in state mindfulness, self-objectification, physical self-concept, and reasons for exercise. Regression analysis was used to examine how state mindfulness predicted change in outcome variables. Results: MANOVAs revealed significant decreases in self-objectification and increases in physical self-concept, health/fitness-related reasons for exercise, and state mindfulness. Further, results indicated that mindfulness during exercise was linked with decreases in self-objectification and increases in more internal reasons for exercise over time. Conclusions: State mindfulness plays a role in predicting change in self-objectification and reasons for exercise during yoga practice. Highlights: Self-objectification decreased across 8-weeks of yoga participation. Physical self-concept and health/fitness reasons for exercise increased during yoga participation. Mindfulness during yoga predicted decreases in self-objectification. Mindfulness during yoga predicted increases in internal reasons for exercise.